Step-by-step explanation:
The function is given below as
![g(x)=6x^3+9x^2-360x](https://img.qammunity.org/2023/formulas/mathematics/college/9e6podk6oirda4n8h5tu231qeh21c2xm1b.png)
To find g'(x) , we will have
![\begin{gathered} g(x)=6x^(3)+9x^(2)-360x \\ g^(\prime)(x)=18x^2+18x-360 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/90ws9nxamwf6wwtw63c17p38n53bo4cmzw.png)
Hence,
The final answer is
![g^(\prime)(x)=18x^(2)+18x-360](https://img.qammunity.org/2023/formulas/mathematics/college/988y3ui219lohvyfimv9tyjpqhz4xrgp20.png)
Part 2:
Find g''(x)
To find g''(x) we will so the calculation below
![\begin{gathered} g^(\prime)(x)=18x^(2)+18x-360 \\ g^(\prime)^(\prime)(x)=36x+18 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ih2gnac0x98zwp9w2bha6mxjtq2qcoxvia.png)
Hence,
The final answer is
![g^(\prime)^(\prime)(x)=36x+18](https://img.qammunity.org/2023/formulas/mathematics/college/2ecjnu3jep9lp6xk5q6030x9qz1n37t4i1.png)
Part 3:
Evaluate g''(-5)
To do this, we will put x= -5 in g''(x)
![\begin{gathered} g^(\prime)^(\prime)(x)=36x+18 \\ g^(\prime\prime)(-5)=36(-5)+18 \\ g^(\prime\prime)(-5)=-180+18 \\ g^(\prime\prime)(-5)=-162 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xz7eyl82ullw40xu60n9wyqkac4lh8ykyd.png)
Hence,
The final answer is
![g^{\operatorname{\prime}\operatorname{\prime}}(-5)=-162]()